Juglone Attenuates CCl₄‐Induced Hepatic Injury in Mice With Associated Modulation of Oxidative Stress and Inflammasome‐Related mRNA Expression. - Sohail, Aamir; Sufyan, Raza; Asim, Muhammad; Khan, Mehroz; Altaf, Aleena; Haq, Muhammad Ehsan Ul; Arshad, Maimoona; Khalil, Atif Ali Khan; Ullah, Imran; Banerjee, Baisakhi (BioMed Research International, 2026)
Carbon tetrachloride–induced liver injury is a well‐established model of toxic hepatitis, characterized by marked oxidative and inflammatory damage. It remains a relevant experimental system because broadly effective therapeutic options are still limited. Juglone, a natural naphthoquinone derived from Reynoutria japonica, has demonstrated antioxidant and anti‐inflammatory potential. However, mouse evidence combining standard liver injury measures with stress‐ and cell‐death gene profiling remains limited. Building on juglone studies in injury and fibrosis, we tested juglone in a CCl4 model. Male C57BL/6 mice were assigned to normal, vehicle, CCl₄, silymarin (200 mg/kg), and juglone (8 mg/kg) groups, and CCl₄ (in corn oil) was administered intraperitoneally. Endpoints included body weight, serum liver enzymes and lipid profile, H&E histology, and RT‐qPCR panels for inflammatory, pyroptosis‐associated, ER stress and autophagy‐linked, apoptotic, oxidative‐stress, and profibrotic transcripts. CCl₄ exposure was associated with weight loss, enzyme elevation, dyslipidemia, and architectural disruption, whereas juglone treatment was associated with improved biochemical indices and histology alongside coordinated downregulation of inflammatory/pyroptosis‐related transcripts (including Il-1β, Il-6, Nlrp3, and Gsdmd) and moderation of ER stress/autophagy and apoptosis‐linked transcripts, with downregulation of profibrotic transcripts (Acta2, Mmp2, and Tgfβ1). In this mouse CCl₄ model, juglone treatment was associated with reduced serum and tissue injury signatures together with changes in stress and inflammation‐linked transcriptional programs. Because the molecular findings are primarily based on RT‐qPCR, these results are best interpreted as gene‐level associations compatible with modulation of oxidative stress, inflammasome‐ and pyroptosis‐related mRNA expression, ER stress responses, apoptosis‐linked transcripts, and remodeling‐associated transcripts, rather than as confirmed pathway inhibition or established antifibrotic activity. These data support juglone as a hepatoprotective candidate and identify protein‐level and functional validation as important next steps.